PENGEMBANGAN SISTEM MONITORING PENGELOLAAN SAMPAH RUANG KELAS OTOMATIS STUDI KASUS SMK BINA PUTRA MANDIRI - Soma; Ludina, Soma; Faozi, Khanif (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
Waste is a common problem frequently encountered in school environments, including at SMK Bina Putra Mandiri. The manual waste management process often causes several issues such as delayed collection, waste accumulation, and inefficiency in utilizing sanitation resources. To address these problems, this research aims to develop an automatic classroom waste management monitoring system based on the Internet of Things (IoT). The system is built using an ESP32 microcontroller, ultrasonic sensors, and a servo motor to detect waste volume in real-time and automatically control the trash bin lid mechanism. Sensor data are transmitted to a web-based dashboard built with Bootstrap SB Admin 2 via the MQTT protocol, allowing school administrators to monitor the condition of all trash bins centrally and efficiently. The development process applies the Rapid Application Development (RAD) method, which emphasizes fast and gradual design and testing based on user feedback. The implementation results show that the system can display the waste bin’s capacity level with high accuracy and automatically send notifications when the bin is full. Additionally, the system can record historical data to support the school’s cleanliness evaluation process. The implementation of this system makes waste management more efficient, organized, and supports the application of IoT technology in creating a cleaner and more sustainable school environment. Keywords: Monitoring System, IoT, ESP32, Ultrasonic Sensor, Rapid Application Development (RAD), Waste Management.